2023
DOI: 10.3390/microorganisms11082058
|View full text |Cite
|
Sign up to set email alerts
|

Genome Analysis and Physiology of Pseudomonas sp. Strain OVF7 Degrading Naphthalene and n-Dodecane

Abstract: The complete genome of the naphthalene- and n-alkane-degrading strain Pseudomonas sp. strain OVF7 was collected and analyzed. Clusters of genes encoding enzymes for the degradation of naphthalene and n-alkanes are localized on the chromosome. Based on the Average Nucleotide Identity and digital DNA–DNA Hybridization compared with type strains of the group of fluorescent pseudomonads, the bacterium studied probably belongs to a new species. Using light, fluorescent, and scanning electron microscopy, the ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Many studies reported that some microorganisms can degrade both PAHs and alkanes [ 21 , 22 ]. Moreover, many studies found that some microorganisms included the PAH and alkane degradation genes, such as benzene, toluene, ethylbenzene, xylene, and naphthalene, can be linked to similar genes, and isolated the function microorganisms in different environments [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies reported that some microorganisms can degrade both PAHs and alkanes [ 21 , 22 ]. Moreover, many studies found that some microorganisms included the PAH and alkane degradation genes, such as benzene, toluene, ethylbenzene, xylene, and naphthalene, can be linked to similar genes, and isolated the function microorganisms in different environments [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many studies found that some microorganisms included the PAH and alkane degradation genes, such as benzene, toluene, ethylbenzene, xylene, and naphthalene, can be linked to similar genes, and isolated the function microorganisms in different environments [ 23 , 24 ]. For example, Ivanova et al reported that Paraburkholderia aromaticivorans strain BN5 included a total of 29 monooxygenase and 54 dioxygenase genes related to the biodegradation of different hydrocarbons [ 21 ]. Therefore, the utilization of the microorganisms that degraded the PAHs has been a focus worldwide.…”
Section: Introductionmentioning
confidence: 99%